Safety, tolerability, and immunogenicity of a 4-antigen Staphylococcus aureus vaccine (SA4Ag): Results from a first-in-human randomised, placebo-controlled phase 1/2 study. Issue 2 (5th January 2017) - Frenck, Robert W.; Creech, C. Buddy; Sheldon, Eric A.; Seiden, David J.; Kankam, Martin K.; Baber, James; Zito, Edward; Hubler, Robin; Eiden, Joseph; Severs, Joseph M.; Sebastian, Shite; Nanra, Jasdeep; et al.
Highlights: SA4Ag is a novel multiantigen vaccine that targets S. aureus virulence factors. A single dose of SA4Ag was well-tolerated in healthy adults aged 18–64 years. A robust functional immune response was elicited to each vaccine component. Antibody rise was rapid and sustained after one dose of SA4Ag vaccine. SA4Ag is a promising candidate vaccine to prevent invasive S. aureus infections. Abstract: Background: A prophylactic Staphylococcus aureus four-antigen vaccine (SA4Ag) is under development for prevention of invasive S. aureus disease. A preliminary S. aureus three-antigen vaccine (SA3Ag) was reformulated to include a novel manganese transporter protein (MntC or rP305A). This study describes the first-in-human dose-finding, safety, and immunogenicity results for SA4Ag. Methods: In this double-blind, sponsor-unblind, placebo-controlled, phase 1/2 study, 454 healthy adults aged 18–64 years were randomised to receive a single dose of one of three formulations of SA4Ag with escalating dose levels of rP305A or placebo. Functional immune responses were measured using opsonophagocytic activity (OPA) killing and fibrinogen-binding inhibition (FBI) assays; antigen-specific immunogenicity was assessed using a four-plex competitive Luminex® immunoassay (cLIA). Results: A high proportion of SA4Ag recipients met the pre-defined antibody thresholds for each antigen at Day 29. A substantial and dose-level dependent immune response was observed for rP305A, with up to 18-fold rises in cLIA titres at Day 29. Robust functional responses were demonstrated, with >80-fold and >20-fold rises in OPA assay titres at Day 29 using S. aureus strains expressing capsular polysaccharide serotypes 5 and 8, respectively. Durable antibody responses were observed through month 12, gradually waning from peak levels achieved by days 11–15. SA4Ag was well tolerated, and no vaccine-related serious adverse events were reported. Conclusions: Single-dose vaccination of SA4Ag in healthy adults aged 18–64 years safely induced rapid and robust functional immune responses that were durable through month 12, supporting further development of this vaccine. Trial registration number: NCT01364571